2016
DOI: 10.1002/pola.28028
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the adsorption and fluorescence properties of aminal‐linked porous organic polymers through N‐heterocyclic group decoration

Abstract: Aiming at tuning the adsorption and fluorescence properties of targeted porous organic polymer, four new aminal-linked porous organic polymers (NAPOPs) were synthesized through the reaction of 1,4-Bis(4,6-diamino-s-triazin-2-yl) benzene (BATB) with four kinds of aldehydes substituted with different N-heterocyclic groups. Among the polymers, NAPOP-3 decorated with 5-phenyl-tetrazole group shows the largest CO 2 adsorption capacity (2.52 mmol g 21 at 273 K and 100 kPa) because of its relative large surface area,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…The nitrogen adsorption/desorption analysisw as performed to analyze the specific surface area with architecturalr igiditya nd permanent porosity of TrzMOP.T he N 2 adsorption/desorption isotherm of TrzMOP and recycled TrzMOP matrix were represented in Figure 2a nd ESI, Figure S4 which displayed the features of both type Ia nd IV isotherms according to IUPAC nomenclature. [47] At the very low pressure region isotherm shows as harpi ncrease of adsorbed N 2 volume which indicates the presenceo fm icroporosity in the polymeric material. Further,a t very high pressure region as mall hysteresis loop together with large nitrogen uptake suggested the existence of mesoporosity in this material.…”
Section: Porosity and Surface Area Analysismentioning
confidence: 95%
“…The nitrogen adsorption/desorption analysisw as performed to analyze the specific surface area with architecturalr igiditya nd permanent porosity of TrzMOP.T he N 2 adsorption/desorption isotherm of TrzMOP and recycled TrzMOP matrix were represented in Figure 2a nd ESI, Figure S4 which displayed the features of both type Ia nd IV isotherms according to IUPAC nomenclature. [47] At the very low pressure region isotherm shows as harpi ncrease of adsorbed N 2 volume which indicates the presenceo fm icroporosity in the polymeric material. Further,a t very high pressure region as mall hysteresis loop together with large nitrogen uptake suggested the existence of mesoporosity in this material.…”
Section: Porosity and Surface Area Analysismentioning
confidence: 95%
“…The moderate capacity originated from the low surface area. It was found that nitrogen-rich polymer favored the sorption toward iodine owing to the stronger interaction between nitrogen atom and electron-deficient I2 [4,[32][33]. The inserted images in Figure 4 showed the color change of I2-cyclohexane (1 mg ml -1 ) solution after adding 25 mg of CMOP-1 and CMOP-2.…”
Section: Gas Sorption Capacitymentioning
confidence: 99%
“…Zhang et al synthesized polymers with N-heterocyclic groups (NAPOPs). NAPOP-1 and NAPOP-3 exhibit high adsorption toward iodine (>240 wt%) and moderate CO2 adsorption [32]. Geng et al constructed novel triazine-based TCMPs by Friedel-Crafts polymerization reaction [33].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on the separationo fC O 2 concerned new adsorbents such as metal-organic frameworks (MOFs), [29][30][31][32][33][34] N-doped porous carbons (NPCs), [35] microporous coordination polymers (MCPs), [36] covalento rganic polymers (COPs), [37][38][39] and porous organic polymers (POPs) [40][41][42] compared to commercial adsorbents (i.e., molecular sieves,a ctivated carbons,a nd silica gel) [43][44][45][46] and relied on theoretical selectivity analysis.E ven with the wide range of utilization in this field, there is still al ack of information on the characteristic behavior of CO 2 adsorption in multicomponent mixtures.T here are no detailed studies for comparison between these types of commercial adsorbents, which are still pioneering materials for CO 2 removal, [47][48][49] related to their partialc omponent uptake performances for awide range of mixturec ombinations and conditions. Molecular sieve zeolite (MSZ) adsorbents are one of the most popular solid adsorbents utilizedn ormally for the separation and purification of multicomponent mixtures.T hese adsorbents have low Si/Al ratios (e.g.,1 3X and 5A zeolite), which results in higher uptake amounts of CO 2 at low pressures ( % 2.5 mmol g À1 at 298 Ka nd 0.1 bar).…”
Section: Introductionmentioning
confidence: 99%